2021
DOI: 10.1088/1361-6463/abd274
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption mechanism of the environmentally friendly insulating gas C5F10O and its main decomposition products on a Cu (1 1 1) surface

Abstract: The perfluoroketone C5F10O, not only has good environmental compatibility, but also has excellent insulation properties and has the potential to replace SF6 in medium and low voltage switchgear. This paper focuses on the compatibility of C5F10O and its main decomposition products with the copper material inside the equipment and specifically constructs several adsorption models of C5F10O and its main decomposition products on a Cu (1 1 1) surface. The adsorption mechanism was studied from a system structure, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Density functional theory (DFT) is an effective way to reveal the interaction mechanism between gases and solids and can guide subsequent experiments [1,25,26]. Wan et al reported on the gas-solid compatibility of CF 3 SO 2 F gas between Cu and Al surfaces, and experimental results also verified the accuracy of theoretical calculations [21].…”
Section: Introductionmentioning
confidence: 94%
“…Density functional theory (DFT) is an effective way to reveal the interaction mechanism between gases and solids and can guide subsequent experiments [1,25,26]. Wan et al reported on the gas-solid compatibility of CF 3 SO 2 F gas between Cu and Al surfaces, and experimental results also verified the accuracy of theoretical calculations [21].…”
Section: Introductionmentioning
confidence: 94%
“…Insulating gas has a long-term coexistence with solid materials inside GIE, which means that once the insulating gas interacts with the solid material, it will lead to the degradation of the performance of solid material, further resulting in gas leakage, equipment corrosion, faults, and serious power accidents [29][30][31]. Moreover, poor gas-solid compatibility may lead to the decomposition of insulation gas and the reduction of the concentration of insulation gas, thereby leading to a decrease in the overall insulation strength of the equipment and serious faults such as insulation failure [32][33][34]. Strong interaction between the decomposing products of insulation gas and solids materials will also pose a threat to the safe operation of insulation equipment to a certain degree [4].…”
Section: Introductionmentioning
confidence: 99%